The Cough Reflex: The Janus of Respiratory Medicine - Sykes, Dominic L.; Morice, Alyn H. (Frontiers in Physiology, 2021)
In clinical practice, we commonly face adversity when encountering dysfunction of the cough reflex. Similar to the ancient Greek deity Janus, it is usually represented with one of two opposing ‘faces’. Continual aberrant activation of the cough reflex, also known as chronic cough, can cause great detriment to quality of life and many of these patients are left misdiagnosed and undertreated. In contrast, loss of normal functioning of the cough reflex is the cause of a significant proportion of mortality in the elderly, primarily through the development of aspiration pneumonia. In this review we aim to discuss both hyper- and hypo-activation of the cough reflex and how the paradigm of airway reflux and chronic aspiration may be involved in both the aetiology and sequalae of both disease states. We detail the physiological and pharmacological mechanisms involved in cough, and how the recent development of P2X3 receptor antagonists may lead to the first pharmaceutical agent licensed for chronic cough. The treatment and prevention of loss of the cough reflex, which has been largely neglected, is also discussed as novel low-cost interventions could help prevent a number of hospital and domiciliary deaths from both acute and chronic aspiration.